2007
DOI: 10.1002/cncr.23007
|View full text |Cite
|
Sign up to set email alerts
|

Health professional and consumer views on involving breast cancer patients in the multidisciplinary discussion of their disease and treatment plan

Abstract: BACKGROUND.The aim was to obtain the views of health professionals and patients about the concept of involving breast cancer patients in the multidisciplinary (MD) treatment planning meeting.METHODS.Breast cancer surgeons, nurses, oncologists, and patient advocates completed a mailed questionnaire.RESULTS.The majority of breast cancer health professionals and patient advocates support shared decision‐making (58%–62%). However, less than a third of surgeons (32%), medical (25%), and radiation oncologists (24%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 26 publications
4
80
1
3
Order By: Relevance
“…During this process, physicians and patients share information and regarding the patient's disease, risks and benefits of treatment options, personal values and priorities regarding treatment, and ultimately reach an agreement on the treatment to implement [2,3]. Studies have shown that shared decision-making could provide a number of benefits for patients, including a greater sense of personal control, more satisfaction, and better compliance with treatment, and consequently better outcomes [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…During this process, physicians and patients share information and regarding the patient's disease, risks and benefits of treatment options, personal values and priorities regarding treatment, and ultimately reach an agreement on the treatment to implement [2,3]. Studies have shown that shared decision-making could provide a number of benefits for patients, including a greater sense of personal control, more satisfaction, and better compliance with treatment, and consequently better outcomes [4,5].…”
Section: Introductionmentioning
confidence: 98%
“…Certain pathology results are of recognized interest in tumoral assessment: thickness, certain histologic forms, expression of certain antigens, etc; • imaging file: usually, all examination results available will be looked at during the meeting, as a final check, which may reveal a suspect element: metastasis, doubtful image, suspicion of second tumor, etc; • general health status and assessment of capacity to withstand treatment: analysis of all complementary examinations performed at initial assessment; • opinion of patient's usual physician, provided directly or reported to a MDTM member. The patient's own physician is aware of the patient's socioeconomic situation, capacities and support; • epidemiological and social data: private and family life, support, friends and relatives; • the possible interest of the patient being present at the MDTM is a matter of debate [12,13] (level of evidence: 4).…”
Section: Guidelinementioning
confidence: 99%
“…Studies report that health professionals feel they have to modify their medical language in the presence of patients and cannot discuss treatment options in the same manner. This may lead, for example, to less accurate reporting or underemphasizing aggressive radiological or histopathological features, which could cause the non-optimal care of patients [9,11,12]. An increase in anxiety in patients participating in tumor boards could not be confirmed [12].…”
Section: Introductionmentioning
confidence: 99%
“…Assumed patient distress, concerns about possible effects on the decision-making processes (especially if opposing opinions between board members exist), and resource intensiveness (meetings are time consuming) are juxtaposed to patient empowerment, better informed patients, greater patient involvement in decision-making, and improved communication between patients and care providers [9,10,11,12]. Health care professionals seem to be less supportive of patient participation in tumor board meetings, whereas patient advocates and nurses support this approach [11]. Studies report that health professionals feel they have to modify their medical language in the presence of patients and cannot discuss treatment options in the same manner.…”
Section: Introductionmentioning
confidence: 99%